Accuracy of the Positional Activity Logger 2 (PAL2) to identify human posture and movement - Lythgo, N.; Benson, A.; Gordon, B. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
This study investigated the accuracy of the Positional Activity Logger 2 (PAL2, ProMed Pty Ltd) to identify activity. Eighteen healthy adults participated in this study. Activities were performed three times in random order for durations ranging from 10 to 110 s and were simultaneously recorded by a PAL2 (10 Hz) and Vicon System (120 Hz). The PAL2 correctly identified all activities. Significant duration differences were found for lying, running, sitting and standing (p=0.001). No significant duration differences were found for walking. Mean absolute errors ranged from 3.27 to 5.40 s. The validity of the PAL2 was also assessed with ICCs. It was found to be high for lying and running (ICC=0.87, ICC=0.94, p=0.0001), good for sitting and standing (ICC=0.74, ICC=0.76, p=0.0001) yet low for walking (ICC=0.58, p=0.001). Overall, the PAL2 exhibited good accuracy.